Pertek Baysungur Bey Mosque - Uzun, Celalettin (Fırat University, 2025)
The mosque located in the Pertek district of Tunceli province, constructed in 1577 by Baysungur Bey, the Sanjak Bey of Pertek, served as the largest place of worship in the city during the Ottoman period. It functioned not only as a religious space but also as a central hub for social and cultural life. The mosque became a defining element of the urban fabric to the extent of giving its name to the neighborhood in which it resides. Due to its central location and size, it transformed into a space where social interactions intensified, thereby playing a significant role in shaping local life. Faced with the danger of being flooded by the construction of the Keban Dam in the 1970s, the building was moved in pieces and rebuilt in its present location with the cooperation of the General Directorate of Foundations and the Middle East Technical University. Within the scope of the study, the architectural features of the mosque, the management structure of the foundation, its sources of income and the distribution of duties of the mosque staff are analysed. In this context, the historical process of the Baysungur Bey Mosque and its foundation in the Ottoman period and its position in social life were analysed, and an important example was put forward within the framework of the mosque-foundation relationship in provincial cities.

Tunceli ilinin Pertek ilçesinde yer alan ve 1577 yılında Pertek Sancakbeyi Baysungur Bey tarafından inşa ettirilen cami, Osmanlı döneminde şehrin en büyük ibadethanesi olma özelliği taşımaktaydı. Cami, yalnızca dini bir mekân olarak değil, aynı zamanda sosyal ve kültürel hayatın merkezi olarak işlev görmüştür. Bulunduğu mahalleye ismini verecek ölçüde kentsel dokuda belirleyici bir unsur olmuştur. Cami, merkezi konumu ve büyüklüğü sayesinde, toplumsal etkileşimin yoğunlaştığı bir alan hâline gelerek yerel yaşamın şekillenmesinde önemli rol oynamıştır. 1970’li yıllarda Keban Barajı’nın inşasıyla sular altında kalma tehlikesiyle karşı karşıya kalan yapı, Vakıflar Genel Müdürlüğü ve Orta Doğu Teknik Üniversitesi iş birliğiyle parçalar hâlinde taşınarak bugünkü yerine yeniden inşa edilmiştir. Çalışma kapsamında caminin mimari özellikleri, vakfın yönetim yapısı, gelir kaynakları ve cami çalışanlarının görev dağılımı incelenmiştir. Bu bağlamda, Baysungur Bey Camii ve ona bağlı vakfın Osmanlı dönemindeki tarihsel süreci ile sosyal hayattaki konumu analiz edilerek, taşra şehirlerinde cami-vakıf ilişkisi çerçevesinde önemli bir örnek ortaya konmuştur.
Pertek Baysungur Bey Camii
Keywords: Early Modern Urban History; Yeniçağ Kent Tarihi